Organização de controle social no desenvolvimento das multiplas funções do meio rural: o caso da Ecosul - Sendtko, Stefano (2020)
The view on the rural environment has undergone transformations, and new perspectives are emerging with the objective of better understanding it, and thus synthesizing policies consistent with singular realities, seeking an inclusive and sustainable rural development. A broad view of the rural environment that encompasses productive, economic, environmental, social and cultural issues is the central point of Agricultural Multifunctionality (MFA), a field of study that seeks to elucidate other “functions” of the rural environment that go beyond food production. In order to understand the internal and external dynamics of farming families that are part of a Social Control Organization (OCS) from the perspective of the MFA, this research analyzed OCS Ecosul, located in the APASA settlement, in the municipality of Pitimbu-PB. Through tools with participatory methodologies, such as the Participative Rural Diagnosis (DRP), historical diagram, semi-structured interviews, and guided visits, it was possible to observe that OCS enabled the opening of new markets, contributing to the economic strengthening of the group and ensuring the maintenance of the social fabric, encouraged the preservation of forests and guaranteed the non-use of pesticides, contemplating issues related to biodiversity. At the same time, there was a low level of cooperation among OCS members on issues that go beyond “certification” and commercialization, which generates deficiencies in several aspects.